Trends in anxiety among adults in the United States, 2008–2018: Rapid increases among young adults - Goodwin, Renee D.; Weinberger, Andrea H.; Kim, June H.; Wu, Melody; Galea, Sandro (Journal of psychiatric research, 2020)
In a time of global uncertainty, understanding the psychological health of the American public is imperative. There are no current data on anxiety trends among adults in the United States (US) over time. This study aimed to investigate prevalence of anxiety among US adults from 2008 to 2018. Data from the National Survey on Drug Use and Health (NSDUH), which is an annual, cross-sectional survey on substance use and mental health in the US, were analyzed in 2020. Prevalence of past-month anxiety was estimated among those ages ≥18, by survey year from 2008 to 2018. Time trends were tested using logistic regression. Anxiety increased from 5.12% in 2008 to 6.68% in 2018 (p < 0.0001) among adult Americans. Stratification by age revealed the most notable increase from 7.97% to 14.66% among respondents 18–25 years old (p < 0.001), which was a more rapid increase than among 26–34 and 35–49 year olds (differential time trend p < 0.001). Anxiety did not significantly increase among those ages 50 and older. Anxiety increased more rapidly among those never married and with some college education, relative to their respective counterparts. Apart from age, marital status and education, anxiety increased consistently among sociodemographic groups. Anxiety is increasing among adults under age 50 in the US, with more rapid increase among young adults. To prepare for a healthier adulthood and given direct and indirect (via 24/7 media) exposure to anxiety-provoking world events, prophylactic measures that can bolster healthy coping responses and/or treatment seeking seem warranted on a broad scale. •Anxiety increased from 2008 to 2018 among American adults.•Nearly 7% of adults and 15% of young adults reported anxiety in 2018.•Anxiety increased most rapidly among young adults ages 18–25 years old.•Anxiety did not significantly increase among individuals 50 years old and older.